The Effectiveness of a Modified Complete Decongestive Therapy Program in the Treatment of Lymphedema Cases - Safaa A. Mahran; Sabah S. Moshref (Journal of King Abdulaziz University: Medical Sciences, 2023)
This study aims to detect the efficacy of a modified complete decongestive therapy program on the improvement of the circumferential measures of the lymphedematous limbs. A prospective observational and interventional study; twenty-six patients with unilateral lymphedema of the extremities both primary and secondary were enrolled. All patients were treated with 6 sessions of complete decongestive therapy on a two-phase program. The first phase consists of meticulous skin care, manual lymphatic drainage, exercises and compression bandages. Phase 2 of self-care program. Circumferential measures of the affected limb were taken as an outcome measure; recorded before and 12 weeks after the application of the decongestive therapy. In both, primary and secondary lymphedema, the modified complete decongestive therapy resulted in a significant reduction (p < 0.05) in the circumference of the affected limb. The circumferential measures of the involved limbs after treatment were (79.69 ±11.92) and (107.68 ± 24.98), consecutively: comparative to the pretreatment measures of (85.14 ± 7.48) for the upper limbs and (113.71 ± 26.91) for the lower limbs. In conclusion, application of a complete decongestive therapy, per available recourses, in a short course or a modified regimen can help in treating primary and secondary lymphedema of the extremities.